2022
DOI: 10.1038/s41467-022-35324-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and reversible optogenetic silencing of synaptic transmission by clustering of synaptic vesicles

Abstract: Acutely silencing specific neurons informs about their functional roles in circuits and behavior. Existing optogenetic silencers include ion pumps, channels, metabotropic receptors, and tools that damage the neurotransmitter release machinery. While the former hyperpolarize the cell, alter ionic gradients or cellular biochemistry, the latter allow only slow recovery, requiring de novo synthesis. Thus, tools combining fast activation and reversibility are needed. Here, we use light-evoked homo-oligomerization o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Taken together, our results demonstrate that PdCO is a rapid, reversible and versatile optoGPCR that mediates efficient silencing of glutamatergic and neuromodulatory synaptic transmission in diverse cell types in vitro and in vivo that expands and complements the collection of presynaptic optogenetic tools 16,59 . For manipulating the presynapse, PdCO could potentially serve as a suitable template to create optoGPCR chimeras with altered signaling specificity by exchanging the intracellular GPCR interface as previously demonstrated for other rhodopsin GPCRs [60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Discussionmentioning
confidence: 60%
“…Taken together, our results demonstrate that PdCO is a rapid, reversible and versatile optoGPCR that mediates efficient silencing of glutamatergic and neuromodulatory synaptic transmission in diverse cell types in vitro and in vivo that expands and complements the collection of presynaptic optogenetic tools 16,59 . For manipulating the presynapse, PdCO could potentially serve as a suitable template to create optoGPCR chimeras with altered signaling specificity by exchanging the intracellular GPCR interface as previously demonstrated for other rhodopsin GPCRs [60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Discussionmentioning
confidence: 60%
“…Taken together, we demonstrated that PdCO is a rapid, reversible, and versatile optoGPCR that mediates inhibition of synaptic transmission efficiently in diverse cell types in vitro and in vivo. With activation time constants in the sub 100-ms and inactivation switching times <10 s, PdCO serves as a fast inhibitory optoGPCR for precise presynaptic inhibition that expands and complements the collection of established and recently developed presynaptic optogenetic tools 16,57 . For manipulating the presynapse, PdCO could potentially serve as a suitable template to create optoGPCR chimeras with altered signaling specificity by exchanging the intracellular GPCR interface as previously demonstrated for other rhodopsin GPCRs [58][59][60][61][62][63][64][65][66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Light-sensitive Gi proteins, such as eOPN3 127 and PPO, 128 can suppress synaptic transmission when expressed presynaptically and are potentially usable with two-photon excitation, although they may cause effects via activation of Kir channels at presynapses. In this respect, opto-SynC, 129 which uses light-evoked homo-oligomerization of cryptochrome CRY2 to cluster synaptic vesicles and inhibit exocytosis, would be completely independent of membrane potential. If the opposite is also possible [i.e., photoactivation of Gs and Gq proteins (opto-XR 130 ), photoactivation of cAMP (bPAC), 131 or light-evoked clustering of synaptic proteins] and exocytosis can be facilitated with two-photon targeted photostimulation, it would be possible to stimulate targeted synapses.…”
Section: Closed-loop Experiments At the Synaptic Levelmentioning
confidence: 99%